Vocational Education Implementation in Mechanical Integrity: SKID Tank Testing and Occupational Safety Standards - Hanif, Yafi Nur; Pramono, Agus; Irawan, Anton (Universitas Negeri Padang, 2025)
This study assessed the operational feasibility of a horizontal cylindrical pressure vessel used for liquefied petroleum gas (LPG) storage at PT. XYZ in Yogyakarta. The evaluation included data collection, visual inspection, thickness measurement, and the calculation of the Maximum Allowable Working Pressure (MAWP) following the ASME Section VIII Division I-UG-27 standard. Results indicated that the vessel’s actual shell thickness of 14.8 mm exceeded the minimum required thickness of 14.66 mm, and the head thickness of 16.4 mm was above the required 14.57 mm, confirming structural adequacy. The calculated MAWP for the cylindrical shell was 1.78 MPa (18.14 kg/cm²) and 1.99 MPa (20.29 kg/cm²) for the ellipsoidal head—both higher than the design pressure of 1.765 MPa (18 kg/cm²). Additionally, hydrostatic testing at 23.40 Kg/cm² (about 30% above the design pressure) showed no leakage or deformation, validating the vessel’s mechanical integrity. Additionally, the unit complied with Occupational Safety and Health (OHS) dan pressure vessel design regulations, ensuring its safety for continued use. This research underscores the importance of vocational education in technical engineering, particularly in pressure vessel testing and adherence to safety standards. By integrating comprehensive training, professionals are better equipped to ensure the structural integrity and safe operation of pressure vessels in industrial settings. The study provides essential insights into maintaining safety and operational efficiency in pressure vessel applications.